A Multi-criteria optimization proposal for aid allocation: combining donor and recipient interests - Yolanda Muñoz-Ocaña; Mercedes Torres Torres Jiménez; Mariano Carbonero-Ruz; Ana M. Pacheco-Martínez (Revista de Economía Mundial, 2022)
It is well known that donors pursue different objectives (altruistic objectives or those based on recipient, and donor interests) in granting their aid. This study proposes an innovative tool that enables a combination of both types of objectives, allowing each donor (bilateral or multilateral) to better understand, optimise and target the distribution of its ODA according to the interests of both parties to the transaction (donor and recipient). This tool uses concentration curves and Suits’ indices to determine an optimal distribution of aid through the development of a constrained optimisation program that encompasses all of its purposes. Furthermore, used at the aggregate level, this tool could facilitate donor coordination to achieve international development goals.